Satisfacción laboral y el compromiso organizacional en los colaboradores de la contraloría de la ciudad de Iquitos año 2024 - Díaz Linares, Jose Luis (2025)
This study aims to determine the relationship between job satisfaction and organizational commitment among employees of the Comptroller's Office of the City of Iquitos in 2024. A quantitative, basic and explanatory research approach was carried out, with a non-experimental and cross-sectional correlational design. The sample consisted of employees of the institution, who were given a structured questionnaire to evaluate both variables. The results showed a high and statistically significant positive correlation between job satisfaction and organizational commitment, with a Spearman coefficient of r = 0.761 and a significance level of p = 0.000, confirming that as job satisfaction increases, organizational commitment also strengthens. These findings highlight the importance of implementing strategies to improve the work environment, recognition, and development opportunities within the institution, in order to optimize organizational performance and stability.